Mixture of Carrot Flour and Brokoli Flour on Acceptance and Nutrients of Nuggets Catfish - Putri Dirayati; Eva Fitriyaningsih (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2022)
Making nuggets from catfish requires additional ingredients that act as fillers and binders in addition to herbs and spices, the filler commonly used is flour. Carrots and broccoli have a very distinctive aroma so that by processing them into flour the aroma of carrots and broccoli can be reduced. Both vegetables have a lot of nutrient content, one of the high nutrients in both vegetables is Vitamins A and C. The aims of this researsh was to determine the physical quality of catfish nuggets with the addition of broccoli flour carrot flour. The experimental design used in this study was a non-factorial Completely Randomized Design (CRD) with 3 treatments, namely the addition of carrot flour and broccoli flour with different amounts. Based on the results of the variance, it was found that the color with the highest average value was 3.82, for taste with an average value of 3.60, for aroma with an average value of 3.88, for texture with an average value of 3.83. in the chemical test with an average value of 2.13. Catfish nuggets with the addition of carrot and broccoli flour had a significant effect on the color, aroma, and texture of catfish nuggets. It is hoped that further research will be carried out on catfish nuggets using the same temperature in each treatment, and it is hoped that when frying catfish nuggets the oil used is replaced in each treatment, which may affect the organoleptic test of catfish.